Implementasi Imprest Fund pada Sistem Akuntansi kas Kecil berbasis Web menggunakan Metode Blacbox Alpha Testing - Atep Hidayat; Yoga Megasyah; Deni Solihin (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2026)
The development of information technology has significantly transformed accounting systems, including petty cash management. This research aims to implement the Imprest Fund method in a web-based petty cash accounting system to enhance the efficiency and accuracy of financial transaction recording. which currently manages petty cash using manual methods, making it prone to recording errors and inefficiencies in financial reporting. The research methodology follows the Rational Unified Process (RUP) approach, consisting of the Inception, Elaboration, Construction, and Transition phases. The expected outcome of this study is the development of a web-based petty cash accounting information system that improves transaction recording efficiency, facilitates audits, and enhances transparency in operational fund management. With this system, Perumda Air Minum Tirta Raharja can reduce recording errors and improve the accuracy and effectiveness of petty cash management.